2012
DOI: 10.1039/c1py00419k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a biodegradable polymer prepared viaradical copolymerization of 2-(acetoacetoxy)ethyl methacrylate and molecular oxygen

Abstract: We describe the synthesis and characterization of a biodegradable and biocompatible polymeric peroxide, poly[2-(acetoacetoxy)ethyl methacrylate] peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…The M n and Đ values of the various polymers are presented in Table . For all three initiating systems, the homo‐ and copolyperoxides show low M n values and relatively high Đ values due to the facile thermal degradation reactions during oxidative polymerization and generation of chain transfer agents such as aldehydes and alcohols that react with the propagating macro‐radicals …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The M n and Đ values of the various polymers are presented in Table . For all three initiating systems, the homo‐ and copolyperoxides show low M n values and relatively high Đ values due to the facile thermal degradation reactions during oxidative polymerization and generation of chain transfer agents such as aldehydes and alcohols that react with the propagating macro‐radicals …”
Section: Resultsmentioning
confidence: 99%
“…Radical copolymerizations of 1,3‐diene monomers, dibenzofulvene, 7,7,8,8‐tetrakis(ethoxycarbonyl)quinodimethane and related monomers with oxygen have also been carried out to prepare alternating copolymers consisting repeat peroxy units in the polymer backbone. In the literature, most vinyl polyperoxides have been synthesized by 2,2′‐azobisisobutyronitrile (AIBN)‐initiated polymerization of vinyl monomers and oxygen at or above 50 °C . However, transition metal complexes such as 5,10,15,20‐tetraphenyl‐21 H ,23 H ‐porphinecobalt(II) pyridine, Co II TPP(Py), and cobalt(II) phthalocyanine pyridine, Co II Pc(Py), have been reported as catalysts for the free radical polymerization of vinyl monomers at ambient temperature and low oxygen pressure .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Furthermore, polyperoxides and their derivatives, including branched and block copolymers, have been applied to various types of degradable functional materials, i.e., dismantlable (de-bondable) adhesives, 8,9 coatings for surface modication, 9,10 and biocompatible materials. 11,12 Matsumoto et al reported that the radical alternating copolymerization of 1,3-diene monomers with oxygen smoothly proceeded in solution under oxygen bubbling, i.e., at atmospheric pressure, in good yields. 13 Considering the fact that the synthesis of polyperoxides using general vinyl monomers requires a high oxygen pressure to increase the yield, 1 the synthesis of polyperoxides using 1,3-diene monomers is versatile, facile, and suitable for practical applications.…”
Section: Introductionmentioning
confidence: 98%
“…The 2-(acetoacetoxy)ethyl methacrylate (AEMA)-based homopolymers and copolymers are of interest because of the presence of β-carbonyl moieties along the side chain [19]. Poly [2-(acetoacetoxy)ethyl methacrylate] (PAEMA) homopolymers self-assembled into a hierarchical superstructure of double-stranded helical tubes through the establishment of hydrogen bridges between adjacent acetoacetoxy groups [20].…”
Section: Introductionmentioning
confidence: 99%